2009
DOI: 10.1093/icb/icp046
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of secondary metabolites by animals: A response to homeostatic challenges

Abstract: We propose that the exploitation of the bioactive properties of secondary metabolites (SMs) by animals can provide a "treatment" against various challenges that perturb homeostasis in animals. The unified theoretical framework for the exploitation of SMs by animals is based on a synthesis of research from a wide range of fields and although it is focused on providing generalized predictions for herbivores that exploit SMs of plants, predictions can be applied to understand the exploitation of SMs by many anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 106 publications
0
71
0
2
Order By: Relevance
“…The roles of tannins in helminths control have been documented (Athnasiadou et al, 2001a;Molan et al, 2003a;Hoste et al, 2006;Cenci et al, 2007;Kotze et al, 2009;Forbey et al, 2009). The nematocidal activity of tannin extracts has also been reported with evidence of anthelmintic properties of condensed tannins by series of in vitro studies (Dawson et al, 1999;Athanasiadou et al, 2001a;Molan et al, 2003b;Ademola and Idowu, 2006) and in vivo studies (Athanasiadou et al, 2000;Butter et al, 2001;Paolini et al, 2003a andKotze et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…The roles of tannins in helminths control have been documented (Athnasiadou et al, 2001a;Molan et al, 2003a;Hoste et al, 2006;Cenci et al, 2007;Kotze et al, 2009;Forbey et al, 2009). The nematocidal activity of tannin extracts has also been reported with evidence of anthelmintic properties of condensed tannins by series of in vitro studies (Dawson et al, 1999;Athanasiadou et al, 2001a;Molan et al, 2003b;Ademola and Idowu, 2006) and in vivo studies (Athanasiadou et al, 2000;Butter et al, 2001;Paolini et al, 2003a andKotze et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Inclusion of medicinal plants in their diet might have implications for the physiology of slow lorises. Forbey et al (2009) suggested that high exploitation of secondary metabolites from plant materials may provide various natural selection advantages for animals and that the ability to utilise these chemicals is more common than previously thought. Wiens et al (2006) already suggested that the extremely low basal metabolism of slow lorises is an adaptation to digest toxic secondary compounds found in their exudate-based diet.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary research highlights the impacts of environmental factors that most affect animal ecology (Poulsen et al 2001) and explains the constraints which limit their distribution. The exploitation of rare or difficult-to-digest resources by some primates may aid in their ability to avoid competition with other animals in their environment (Ganzhorn 2002), and may also lead to evolutionary advantages regarding health and anti-predator de fence systems (Forbey et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Many plant SM have antimicrobial properties (Cowan, 1999), and animals exploit therapeutic SM to mitigate costs of parasitism, infection and other homeostatic challenges (Forbey et al, 2009). Such self-medication has also been demonstrated in various insects (Castella et al, 2008;Lefèvre et al, 2010;Singer et al, 2009) …”
Section: Effect Of Nectar Nicotine On Honeybee Survivalmentioning
confidence: 99%